Bohdan Dziemidok, Filozofia i sztuka życia, Wydawnictwo UMCS, Lublin 2017, ss. 164. - Błaszczyk, Marek (Humaniora. Czasopismo Internetowe, 2020)
Bohdan Dziemidok, Filozofia i sztuka życia, Wydawnictwo UMCS, Lublin 2017, ss. 164.